Flipped classroom and learning outcomes: a systematic review of conditions, mechanisms, and TVET implications - Alzet Rama; Wiki Lofandri (Lentera Negeri, 2025)
The flipped classroom (FC) model restructures instructional time by relocating direct instruction to the pre-class phase via digital media and dedicating in-class time to collaborative, higher-order tasks. Despite a decade of growing research interest, the empirical record remains conspicuously heterogeneous: positive effects coexist with null findings, and the mechanisms distinguishing effective from ineffective implementations remain incompletely theorised. This systematic literature review synthesises empirical research from 2020 to 2025 to examine the conditions under which FC influences learning outcomes cognitive achievement, higher-order thinking skills (HOTS), and student engagement with particular attention to Technical and Vocational Education and Training (TVET) and developing-country higher education contexts. A PRISMA-guided protocol was applied across Scopus, Web of Science, and Google Scholar, yielding 42 included studies subjected to thematic synthesis; 20 key studies are summarised in a structured evidence table. FC produces positive but contextually contingent effects, with effect sizes ranging from g = 0.21 to d = 0.71. Critical moderators include instructional design quality, student self-regulated learning (SRL) capacity, and technology infrastructure. Contradictory findings cluster around compliance failure, novelty effects, and disciplinary mismatch. FC is not inherently effective; its value depends fundamentally on implementation fidelity and learner preparedness. The review introduces the Input–Process–Regulation–Output (IPRO) conceptual framework to guide future research and practice, with particular relevance to TVET and resource-constrained educational settings.